Hubungan Status Depresi Dan Status Gizi Dengan Tekanan Darah Pada Lansia Di Panti Wredha Dharma Bhakti Surakarta - ARNA, Rona Dewi, Endang Nur W, SST., M.Si Med, Eni Purwani, SSi., M.Si (2015)
Introduction : High blood pressure is one of degenerative disease has high morbity and mortalitas. High blood pressure prevalence elderly in Panti Wredha Dharma Bhakti Surakarta in July-August 2015 as much as 32,32 %. Objective : The purpose of the study aims to know the relationship of the depression status and nutritional status with blood pressure elderly in Panti Wredha Dharma Bhakti Surakarta. Research method : The research was an observasional with cross-sectional approach. The sample of the research were 41 elderly of Panti Wredha Dharma Bhakti Surakarta. Simple random sampling was used in the research. The depression status were obtained using geriatric depression scale form. The nutitional status were obtained using antropometry. Results : The research results indicated that the elderly have not normal blood pressure as much as 34,1%, depression status as much as 31,7% and not good nutritional status as much as 41,5%. The result of Chi Square test about the relationship depression status with blood pressure show value p bigger than 0,05 (p=0,142). The result of Chi Square test about the relationship nutritional status with blood pressure show value p bigger than 0,05 (p=0,678). Conclusion : There were no relationship the depression status and nutritional status with blood pressure at elderly in Panti Wredha Dharma Bhakti Surakarta.